Firm Growth and the Spatial Impact of Geolocated External Factors - Empirical Evidence for German Manufacturing Firms - Matthias Duschl; Antje Schimke; Thomas Brenner; Dennis Luxen (Philipps-University Marburg, Department of Geography, 2011)
In this paper the relationship between firm growth and external knowledge sources, such as related firms and universities, is studied. The spatial characteristics of these relationships are examined by geolocating firms into a more realistic relational space using travel time distances and using flexible distance decay function specifications. This approach properly accounts for growth relevant knowledge spillovers and allows for estimating their spatial range and functional form. Applying quantile regression techniques on a large sample of German manufacturing firms, we show that the impact of external factors substantially differ along firms' size, type of knowledge source and growth level.
Keywords: C31; D92; L25; R11; 330; Firm growth; external factors; universities; agglomeration; space; spatial range; distance decay functions; knowledge spillovers; high growth firms; quantile regression